An investigation of the effectiveness of cognitive behavior modification in the reduction of text anxiety - Köksal, Falih. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1984., 1984)
The present study aimed to investigate the effectiveness of Cognitive Behavior Modification in reducing the test anxiety, of twenty (8 male, 12 female) Robert College lycee three students. To asses the level of test anxiety of subjects in pre and post testing, STAI and TAS were used as instruments. The treatment was applied to the subjects in the experimental group while it was witheld from the control group. The hypothesis put forward was that, the decrease of test anxiety in the experimental group on STAI and TAS would be significantly greater than that in the control group. With the application of t-tests the results were found not to support this hypothesis. Various speculations as to the reasons for these findings were discussed and suggestions for further studies were given.
Keywords: Behavior modification.; Cognitive therapy.; Anxiety.